Beyond a bottle of liquid: pesticide dependence in transitional rural China. Issue 8 (2nd August 2016) - Hu, Zhanping; Rahman, Sanzidur
Abstract : Pesticide dependence is a major threat to food safety and local environment. Although numerous studies have explored different causes of pesticide dependence, few have examined how pesticides are locked into agricultural modernisation and rural transformation. Based on a case study of a Chinese village, this paper demonstrates how agricultural modernisation trajectory and rural changes have perpetuated the use of pesticides as necessities in agriculture as well as for farmers' livelihoods. Modern technologies, such as hybrid rice, conservation tillage, changes in crop structure, and reduction of intercropping all contribute highly towards pesticide dependence. The household responsibility system in China has provided the institutional foundation for increased pesticide use. Rural transformations driven by livelihoods diversification have created conducive social spaces for pesticide application. To step out of pesticide dependence, promotion of genetic diversity in agriculture, a reassessment of locational suitability of conservation tillage, institutional strengthening and the promotion of integrated pest management methods are suggested.